Efektivitas Hole of Rainbow untuk Mengembangkan Sosial Emosional Anak Usia 4–5 Tahun - Rahbani, Silma (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
The low level of social-emotional development among early childhood learners at PAUD Al-Ibad, particularly in the areas of self-awareness, social responsibility, and prosocial behavior serves as the background for this study. The research aims to examine the effectiveness of the Hole of Rainbow media in developing the social-emotional aspects of children aged 4–5 years. A quantitative method was employed using a pre-experimental one-group pretest-posttest design, involving 18 children from Group A selected through total sampling. The research instrument consisted of observation sheets, and the data were analyzed using the Paired Sample t-Test. The results show a significant increase in social-emotional scores from the pretest (mean = 22.2) to the posttest (mean = 48.3), with a significance value of ρ = 0.001 (p < 0.05), indicating that the Hole of Rainbow media is effective in enhancing early childhood social-emotional development. These findings are supported by previous research demonstrating the effectiveness of picture story media in similar contexts. The study concludes that educational play-based learning media can positively contribute to the development of children’s social-emotional skills. The implication is that early childhood educators are encouraged to incorporate this media into structured and enjoyable play activities. Furthermore, the study opens opportunities for the development of similar media combined with elements such as music or storytelling to enrich children's learning experiences holistically.